Graphene Oxide Nanoparticles Decorated Pencil Lead as Urea Sensing Electrode - Singh, Saravjeet; Sharma, Minakshi; Singh, Geeta (Asian Journal of Chemistry, 2021)
In present study, a low-cost and steady electrochemical biosensor has been developed based on graphene oxide nanoparticles (GONPs), electrodeposited on the pencil lead electrode (PLE). The physical and morphological studies revealed the nano-scale range of GONPs that has an average grain size/layer thickness of 2.27 nm and agglomeration size of 90-120 nm. Urease enzyme was immobilized on PLE/GONPs electrode after surface treatment with 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC)/N-hydroxysuccinimide (NHS) to impart stable peptide bond. Scanning electron microscopy (SEM) studies demonstrate the difference between unmodified and modified PLE electrodes and depict the spherical, circular and flaky-like morphology. The electrochemical analysis of urea considerably improved on the PLE/GONPs/Ur compared to the untailored PLE electrode. The reported urea biosensor operated in a linear dynamic range between 0.30-50 mM that attained a recognition limit of 0.06 mM and exhibited an advanced exposure sensitivity of 0.814 μA mM-1 cm-2.